The inn at Rose Harbor : a novel - Macomber, Debbie (New York : Ballantine Books, 2012)
Jo Marie Rose opens the Rose Harbor Inn bed and breakfast in Cedar Cove in order to start a new life, but the inn and its first guests bring surprises into Jo's life.
Keywords: Bed and breakfast accommodations -- Fiction; Love stories